Políticas cicloinclusivas e cicloturismo: o caso do Rio de Janeiro (RJ) - Saldanha, Luiz Emerson da Cruz. (2017)
The tourism using bicycle for displacement, also known as cycling tourism, is a market segmentation that grows with considerable representation worldwide. Its benefits range from the movement of the local economy to socio-cultural inclusion and environmental conservation. There are several countries that integrate strategies and plans for tourism and bicycle planning in their public policies. In Brazil, is still common a dissociated view of cycling and tourist planning, even in cities with relevant tourism and great investment in cycling infrastructure – such as the city of Rio de Janeiro. In this context, the present study aims at an understanding of the strategic planning of urban cycling tourism trough the interface of cycling-inclusive policies and the organization of tourism to enable a choice and adaptation of analysis methodologies on cycling networks in tourist destinations. The results obtained from the application of the concepts and methods in Rio de Janeiro are important for the development of Brazilian cycling tourism and for the establishment of new academic studies on the theme.